Estimated footprint of shellfishing activities in Zostera noltei meadows in a northern Spain estuary: Lessons for management. (5th June 2021) - Garmendia, Joxe Mikel; Valle, Mireia; Borja, Ángel; Chust, Guillem; Rodríguez, José Germán; Franco, Javier
Abstract: Intertidal seagrasses often occupy areas of high ecological importance that are also targeted for human activities, such as shellfishing and leisure walking. These activities could affect the growth or survival of seagrass. The society at large lacks knowledge of the ecological relevance of seagrasses and their vulnerability, presenting an obstacle for their conservation. Here, the Oka estuary (Basque Country, N. Spain) is used as a case study to analyse the spatial extent of shellfishing activities in seagrass ( Zostera noltei ). This estuary holds 84% of the intertidal seagrass meadows present in the Basque Country and is visited during the year by professional and recreational shellfishers. Bait digging is legal year-round, and clam digging (by professionals only) from October to February. Human presence over 11 years averaged 17 people on the tidal flat in each daylight hours from August to October. Each professional shellfishing daily trip affected 7.4–21.6 m 2 by fishing and 110–188 m 2 by trampling in seagrass, but was substantially different between clam and bait (crustacean, worm) fishing. Scaling up this area to estimated annual number of shellfishers, 8–69% of the total seagrass area is trampled and 1–9% is dug per year. In comparison to a habitat suitability map for seagrass, 98% of trampling occurred within a very highly suitable area for seagrass presence (i.e., >90%). This pressure could adversely affect seagrass density and prevent the expansion of meadows into areas suitable for seagrass. Management of public impacts to seagrass in this estuary could occur through prohibition of some activities in seagrass and awareness campaigns among shellfishers and walkers. Graphical abstract: Image 1 Highlights: Seagrass surface is declining in the Basque estuaries. Trampling and digging by shellfishers are the main perturbing human factors for Basque seagrasses. Shellfishers trampling and digging on seagrasses is quantified for the Oka estuary. Awareness-raising campaign and some banning measures are proposed to protect and conserve seagrasses in the Oka estuary.